فینۆمینۆلۆجیاوخوێندنەوەیەك بۆدەقی (هەی كەرێكم هەبوو، چ پەیكەر ؟ طەی كەری هەوراز و لێژ)ی نالی توێژینەوەی هەڵهێنجراو لە تێزی دکتۆرا - قادر, عباس محمد; حسين, علی طاهر (Sulaimani Journal for Humanities, 2022)
This research, which is a phenomenological approach to read, is for one of Nali's text in which we tried to discuss it in a theoretical way. Next, we clarified our purpose as idiom and concept; then, talking about phenomenology in association with reading literary texts was also concluded. After that, we analyzed the way we deal with text; subsequently, one of Nali's texts was taken and was evaluated practically. All in all, what we have wanted to progress was mentioned above.